Temperature dependence of some properties of star-branched polymers in confined space. A Monte Carlo study - Romiszowski, P. (Condensed Matter Physics, 2002)
A simulation study of star-branched molecules with 3 arms was performed
in a space confined between two parallel repulsive walls, which were at the
distance d apart. The simulations were performed for chains on a simple
cubic lattice. The chains consisted of N = 49 , 100 and 199 beads. During
the simulations the solvent quality has been varied by means of changing
the segment-segment interactions. Also the thickness of a layer between
the walls has been changed. The results show that there is a coil-to-globule
transition. The transition temperature does not depend on the confinement.
However, the scaling exponents of the radius of gyration of the chains are
sensitive to value d . За допомогою копм’ютерного моделювання досліджено зірково-гіллясті молекули з 3 -х ланцюгів у просторі між двома паралельними
відштовхувальними стінками, розташованими на відстані d одна від
другої. Моделювання проводилося для ланцюгів на простій кубічній
гратці. Ланцюги складалися з N = 49 , 100 і 199 ланок. Якість розчинника під час моделювання регулювалася за допомогою зміни взаємодії між сегментами. Також змінювалася товщина шару між стінками. Результати свідчать про те, що відбувається перехід полімерний
клубок–глобула. Температура переходу не залежить від обмеження
простору. Однак, показники скейлінгу радіусу гірації чутливі до величини d .